Preliminary results of a floating subirrigation system (Aquaforest system) as an alternative to conventional tree nurseries - Augusto, DCC; Engel, Vera Lex [UNESP]; Velini, Edivaldo Domingues [UNESP] (Elsevier B.V., 2004)
A new methodology for tree seedling production (Aquaforest system) based on a continuous floating subirrigation system was developed and tested using creeks with different nutrient levels. Eucalyptus grandis seedlings were produced in water from polluted and clean creeks, and compared to conventional tree nursery production. The growth variables analyzed in the seedling phase were: survival, height, diameter, shoot and root dry weight, leaf area, and root/shoot ratio. Water and substrate were analyzed, as well as leaf nutritional status. Plant survival was 100% in all treatments. Height and diameter were greater in the higher nutrient water treatment. Leaf area and dry weight of plants produced in the higher nutrient water treatment were similar to those of the control. The results showed that polluted water can represent a good nutrient source. The preliminary results show that the Aquaforest system can be a viable alternative for tree seedling production. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: seedling production; subirrigation; Eucalyptus grandis; polluted water